2006
DOI: 10.1002/cbf.1315
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents formaldehyde‐induced neurotoxicity in prefrontal cortex of rats: an immunohistochemical and biochemical study

Abstract: This study was undertaken to investigate the protective effects of melatonin against formaldehyde-induced neurotoxicity in prefrontal cortex of rats. For this purpose, 21 male Wistar rats were divided into three groups. The rats in Group I were used as a control, while the rats in Group II were injected every other day with formaldehyde. The rats in Group III received melatonin daily while exposed to formaldehyde. At the end of 14-day experimental period, all rats were killed by decapitation. The brains of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 45 publications
5
43
0
1
Order By: Relevance
“…In addition, there are available data in the literature regarding the symptoms and side effects of FA on several systems (Table 2). [29][30][31][32][33][34] Effects of formaldehyde on the urinary system The toxic effects of formaldehyde occur in several systems of the body, and both experimental and clinical investigations have attempted to elucidate the toxic effects of formaldehyde on the urinary system. In a study conducted in workers with occupational FA exposure, it was found that there was a significant increase in the incidence of renal cancers among these employees.…”
Section: Formaldehyde Usesmentioning
confidence: 99%
“…In addition, there are available data in the literature regarding the symptoms and side effects of FA on several systems (Table 2). [29][30][31][32][33][34] Effects of formaldehyde on the urinary system The toxic effects of formaldehyde occur in several systems of the body, and both experimental and clinical investigations have attempted to elucidate the toxic effects of formaldehyde on the urinary system. In a study conducted in workers with occupational FA exposure, it was found that there was a significant increase in the incidence of renal cancers among these employees.…”
Section: Formaldehyde Usesmentioning
confidence: 99%
“…4,5,9,10 BRIEF ise DEHB'deki başlıca bozukluk alanı olan ve prefrontal bölge-nin 63 fonksiyonu olan yönetici işlevleri 25,64,65 ölç-mek üzere geliştirilmiştir. İlgili literatürde 16,40 uygulananlardan farklı olarak klinik belirtilere ilişkin davranışsal göstergelerin (CDÖ) tanılamaya olan katkısı, bilişsel göstergelerin (BRIEF) de eklenmesi suretiyle incelendiğinde; farklı formlar ve gruplar için elde edilen farkların %11,10 ve altında kaldığı belirlenmiştir (Tablo 3 ve Şekil 1).…”
Section: Discussionunclassified
“…Chang and Xu [77] and Zararsiz et al [49] suggested that, formaldehyde causes oxidative stress and lipid peroxidation. Their study showed decrease in the activity of superoxide dismutase (SOD), GSH-Px and increase in the concentration of malondialdehyde (MDA) which was consistent with our study.…”
Section: Experimental Studymentioning
confidence: 99%
“…The use of different antioxidants as selenium [31], melatonin [49], vitamin E [85], and omega-3 essential fatty acids [86] were used to counteract FA induced neurotoxicity. Currently reliance on natural products is gaining popularity to combat various physiological threats including oxidative stress, cardiovascular complexities, cancer insurgence, and immune dysfunction.…”
Section: Experimental Studymentioning
confidence: 99%